2019
DOI: 10.1002/aet2.10424
|View full text |Cite
|
Sign up to set email alerts
|

The Keyword Effect: A Grounded Theory Study Exploring the Role of Keywords in Clinical Communication

Abstract: Objectives: Keywords, also known as "buzzwords" or "trigger words," serve as memorable descriptors to associate physical findings with specific diagnoses. These terms, such as "target lesion" and "steeple sign," liken a physical or radiographic finding to a nonmedical comparator as a means to elicit an associated diagnosis. Keywords permeate medical literature and clinical conversations. However, the potential for miscommunicating critical information exists and the impact of keywords on communication-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Because keywords are highlighted summaries of the literature topic and content, the frequency and centrality of keywords generally reflect the intensity of a certain topic that researchers may be concerned with or aim to address in the research field [ 39 ]. The keyword cooccurrence map showed that SARS-CoV-2, COVID-19, saliva, and coronavirus were the most frequent and established extensive links to other keywords (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because keywords are highlighted summaries of the literature topic and content, the frequency and centrality of keywords generally reflect the intensity of a certain topic that researchers may be concerned with or aim to address in the research field [ 39 ]. The keyword cooccurrence map showed that SARS-CoV-2, COVID-19, saliva, and coronavirus were the most frequent and established extensive links to other keywords (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Keywords were manually merged and deleted, such as changing covid-19 to covid 19, and changing sar, sars, virus, coronavirus, infection, respiratory syndrome coronavirus to sars-cov-2. Keywords are high-level summaries of literature content and topics, which could diagnose and activate disease scripts and are an integral part of medical culture and language ( Chan and Eppich, 2020 ). T The results show that research hotspots in the field of COVID-19 genomics mainly focus on covid 19, SRAS-COV-2, protein, RNA, ace2, replication, vaccine, expression, spike protein, transmission, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…3), where student performance is hypothesised to be related to the use of the phrase 'loin to groin' which acts as a buzzword for renal colic. In support of this hypothesis, Chan and Eppich (2020) found that doctors equated keywords (or buzzwords) with studying for undergraduate medical examinations and one of the participants in their study, a junior doctor said '…when we're rst learning clinical medicine, a lot of the patterns that we recognise are in speci c phrases' (Chan and Eppich, 2020). They concluded that keywords can communicate entire diagnoses and activate illness scripts independently of any other information.…”
Section: Discussionmentioning
confidence: 97%